Advanced 3D network of N-doped graphitic carbon with FeNi alloy embedding for high-performance rechargeable Zn-air batteries - Pandikassala, Ajmal; Kurian, Maria; Gangadharan, Pranav K.; Torris, Arun; Kurungot, Sreekumar (Advanced Sustainable Systems, 2024)
Despite the significant progress in Zn-air batteries (ZABs), their widespread use in the rechargeable sector is hindered due to the scarcity of efficient bifunctional oxygen catalysts that can catalyze both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). To address this, an ORR/OER bifunctional electrocatalyst is designed with ultrafine alloyed FeNi nanoparticles encapsulated in a 3D interconnected N- doped carbon network structure, featuring a carbon nitride backbone enclosed in graphitic carbon. The FeNi electrocatalyst (3DFeNiPDC) showed good bifunctional activity toward both ORR and OER in the basic medium with a low overpotential value of 30 mV for ORR and 6 mV for OER compared to its state-of-the-art counterparts Pt/C, and RuO2, respectively. Utilizing 3DFeNiPDC in a rechargeable Zn-air battery (RZAB) yields an open circuit voltage (OCV) of 1.35 V, a maximum power density of 232 mW cm-2, and an energy density of 707 W h kg-1. Additionally, a flexible RZAB employing 3DFeNiPDC demonstrates an OCV of 1.4 V with various bending angles. These finding suggest 3DFeNiPDC as a viable alternative to noble metal-based RZABs, offering superior bifunctional electrocatalytic activity and stability, particularly with its enhanced air-breathing properties facilitating improved operability under practical conditions. The bifunctional electrocatalytic activity of FeNi alloy nanoparticles embedded in a 3D- interconnected N-doped graphitic carbon (3DFeNiPDC) for both oxygen reduction and oxygen evolution is studied. The 3D architecture and core-shell characteristics of FeNi alloy nanoparticles provide better activity and stability for oxygen electrocatalysis. The electrocatalytic activity of 3DFeNiPDC has been exploited for liquid-state and solid-state flexible rechargeable zinc-air batteries. image
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery